Answer:
sin(45°)= AC/9
cos(45°)= BC/9
Step-by-step explanation:
This is a right angle triangle:
∠ABC =∠CAB = 45°
Now
AC= CB
AB = 9 units.
We will apply sines:
sine(45°)= AC/AB
We know that AB = 9 units.
So substitute the value of side AB
sin(45°)= AC/9
Now apply cos(45°)
cos(45°)= BC/AB
Again substitute the value of AB:
cos(45°)= BC/9
Thus the answer is
sin(45°)= AC/9
cos(45°)= BC/9 ....
Answer:
A
E
Step-by-step explanation:
-3(6f - 12) = 36 - 18f
Answer:
Step-by-step explanation:
The given expression is:
-3(6f - 12) = 36 - 18f
To prove that L.H.S=R.H.S:
Multiply -3 (6f-12)
-3(6f)-3(-12)
=-18f+36
=36-18f
Hence it is proved that L.H.S = R.H.S....
what is the simplest form of 3√27a3b7
Answer:
[tex]3ab^2\sqrt[3]{b}[/tex]
if the problem was [tex]\sqrt[3]{27a^3b^7}[/tex].
Step-by-step explanation:
Correct me if I'm wrong by I think you are writing [tex]\sqrt[3]{27a^3b^7}[/tex].
[tex]\sqrt[3]{27a^3b^7}[/tex]
I'm first going to look at this as 3 separate problems and then put it altogether in the end.
Problem 1: [tex]\sqrt[3]{27}=(3)[/tex] since [tex](3)^3=27[/tex].
Problem 2:[tex]\sqrt[3]{a^3}=(a)[/tex] since [tex](a)^3=a^3[/tex]
Problem 3: [tex]\sqrt[3]{b^7}[/tex]. This problem is a little harder because [tex]b^7[/tex]is not a perfect cubes like the others were. But [tex]b^7[/tex] does contain a factor that is a perfect cube. That perfect cube is [tex]b^6[/tex] so rewrite [tex]b^7[/tex] as [tex]b^6 \cdot b^1[/tex] or [tex]b^6 \cdot b[/tex].
So problem 3 becomes [tex]\sqrt[3]{b^6 \cdot b}=\sqrt[3]{b^6}\cdot \sqrt[3]{b}=b^2 \cdot \sqrt[3]{b}[/tex]. The [tex]b^2[/tex] came from this [tex](b^2)^3=b^6[/tex].
Anyways let's put it altogether:
[tex]3ab^2\sqrt[3]{b}[/tex]
What is the measure of angle ABC?
Mrs. Cleary's class is selling candy bars to
raise money for a field trip. The students
in the class set a goal of how much
money they would like to raise.
The following formula describes this
scenario:
where
g = goal for money raised
p = profit made from each candy bar sold
n = number of candy bars sold. The class wants to raise a total of $600. If they sell 600 candy bars , how much profit will they receive from each candy bar ?
Answer:
1
Step-by-step explanation:
Assuming g(n)=pn, and plugging in
g=600 and n=600:
600=p(600)
600/600=p
1=p
profit per candy bar is $1
Which represents the solution set to the inequality 5.1(3 + 2.2x) > –14.25 – 6(1.7x + 4)
Answer:
x > -52.5.
Step-by-step explanation:
5.1(3 + 2.2x) > –14.25 – 6(1.7x + 4)
15.3 + 11.22x > -14.25 - 10.2x - 24
1.02x > -14.25 - 24 - 15.3
1.02x > -53.55
x > -53.55 / 1.02
x > -52.5.
Answer:
(–2.5, ∞)
Step-by-step explanation:
which equation represents a circle?
Answer:
C
Step-by-step explanation:
The equation of a circle centred at the origin is
x² + y² = r² ← r is the radius
Consider
[tex]\frac{x^2}{2^2}[/tex] + [tex]\frac{y^2}{2^2}[/tex] = 1, that is
[tex]\frac{x^2}{4}[/tex] + [tex]\frac{y^2}{4}[/tex] = 1
Multiply through by 4
x² + y² = 4 ← equation of circle
This is the equation of a circle centred at the origin with radius 2
What is the product of 2p + q and -3q - 6p + 1
Answer:
[tex]\large\boxed{(2p+q)(-3q-6p+1)=-3q^2-12p^2-12pq+2p+q}[/tex]
Step-by-step explanation:
Use the distributive property: a(b + c) = ab + ac
[tex](2p+q)(-3q-6p+1)=(2p+q)(-3q)+(2p+q)(-6p)+(2p+q)(1)\\\\=(2p)(-3q)+(q)(-3q)+(2p)(-6p)+(q)(-6p)+2p+q\\\\=-6pq-3q^2-12p^2-6pq+2p+q\qquad\text{combine like terms}\\\\=-3q^2-12p^2+(-6pq-6pq)+2p+q=-3q^2-12p^2-12pq+2p+q[/tex]
coordinates of the vertex
Answer:
(0, 3)Step-by-step explanation:
The vetex form of an equation of a parabola y = ax² + bx + c:
y = a(x - h)² + k
(h, k) - coordinates of a vertex
We have the equation y = 3x² + 3.
y = 3(x - 0)² + 3 → h = 0, k = 3
The table shows the approximate height of a projectile x seconds after being fired into the air.
Which equation models the height, y, x seconds after firing?
y = –10(x)(x – 5)
y = 10(x)(x – 5)
y = –10(x – 5)
y = 10(x – 5)
time in seconds height meters
x y
0 0
1 40
2 60
3 60
4 40
5 0
The equation y = -10 (x) (x - 5) models the height.
Option A is the correct answer.
What is an equation?An equation contains one or more terms with variables connected by an equal sign.
Example:
2x + 4y = 9 is an equation.
66x = 8 is an equation.
We have,
From the table,
We can make ordered pairs in the form of (x, y).
(0, 0), (1, 40), (2, 60), (3, 60), (4, 40), (5, 0).
So,
We will choose the equation that satisfies the ordered pairs.
y = -10 (x) (x – 5)
This can be used as the equation.
For (0, 0), (1, 40), (2, 60), (3, 60), (4, 40), (5, 0)
i.e x = 0, 1, 2, 3, 4, 5
y = -10 x 0 = 0
y = -10 x 1 x -4 = 40
y = -10 x 2 x -3 = 60
y = -10 x 3 x -2 = 60
y = -10 x 4 x -1 = 40
y = - 10 x 5 x 0 = 0
y = 10 (x) (x - 5)
This can not be used since the y value is a negative value.
y = -10 (x – 5)
This is not possible.
y = 10 (x – 5)
This is not possible.
Thus,
The equation y = -10 (x) (x - 5) satisfy the given table values.
Learn more about equations here:
https://brainly.com/question/17194269
#SPJ6
To find which equation models the height of a projectile \( y \) seconds after being fired based on the given data, we can substitute the given x-values (time in seconds) into each equation and check whether the result matches the corresponding y-values (height in meters).
Let's go through each of the given equations and the provided points one by one:
1. Equation \( y = -10(x)(x – 5) \)
When \( x = 0 \), the height \( y \) should be 0.
Substituting the value into the equation, \( y = -10(0)(0 – 5) = 0 \), which matches the given point (0, 0).
When \( x = 1 \), the height \( y \) should be 40.
Substituting the value into the equation, \( y = -10(1)(1 – 5) = -10(-4) = 40 \), which matches the given point (1, 40).
When \( x = 2 \), the height \( y \) should be 60.
Substituting the value into the equation, \( y = -10(2)(2 – 5) = -10(-1) = 60 \), which matches the given point (2, 60).
When \( x = 3 \), the height \( y \) should be 60.
Substituting the value into the equation, \( y = -10(3)(3 – 5) = -10(-2) = 60 \), which matches the given point (3, 60).
When \( x = 4 \), the height \( y \) should be 40.
Substituting the value into the equation, \( y = -10(4)(4 – 5) = -10(-1) = 40 \), which matches the given point (4, 40).
When \( x = 5 \), the height \( y \) should be 0.
Substituting the value into the equation, \( y = -10(5)(5 – 5) = -10(0) = 0 \), which matches the given point (5, 0).
Since all the points match perfectly with the results from Equation 1, we confirm that Equation 1 models the height of the projectile accurately. Therefore, the correct equation is:
\( y = -10(x)(x – 5) \)
This quadratic equation represents a parabolic trajectory, which is typical for the motion of a projectile under gravity, with no air resistance, and assuming that the projectile lands at the same level from which it was fired.
I need some help guys
Answer:
Q1: D
Q2: D
Step-by-step explanation:
Question No 1:
The given sequence is:
-2, 0, 3, 7, ...
We can easily determine that this is not an arithmetic sequence because the common difference between terms is not same.
i.e.
0-(-2) = 0+2 = 2
3-0 = 3
7-3 = 4
As the common difference is not same so the sequqnce is not an arithmetic sequence.
Question no 2:
Given sequence is:
28, 18, 8, -2, ..
We can see that the common difference is -10 i.e 18-28 = -10
And it is same for all numbers.
The standard formula for arithmetic sequence is:
[tex]a_n=a+(n-1)d\\Here\\a = 28\\d=-10\\So,\\a_n=28+(-10)(n-1)\\a_n=28-10n+10\\a_n=38-10n[/tex]
Now for the 52nd term:
[tex]a_{52} = 38-10(52)\\= 38-520\\=-482[/tex] ..
Leila bought 3 bananas, which weighed a total of 3/4 of a pound . if each banana weighed the same amount , what is the weight of each banana ?
Answer:
I think the answer is A
Step-by-step explanation:
Answer:
C.
Step-by-step explanation: The other answer was not right on edge* but i belive that it is C.
For what values of m dose the graph of y=3x^2+7x+m have two x-intercepts?
Answer:
[tex]\large\boxed{m<\dfrac{49}{12}}[/tex]
Step-by-step explanation:
x-intercepts are for y = 0.
Put y = 0 to the equation y = 3x² + 7x + m.
3x² + 7x + m = 0Calculate the discriminant of quadratic equation ax² + bx + c = 0:
Δ = b² - 4ac
if Δ < 0, then an equation has no solution
if Δ = 0, then an equation has one solution
if Δ > 0, then an equation has two solution.
3x² + 7x + m = 0a = 3, b = 7, c = m
Δ = 7² - 4(3)(m) = 49 - 12m
Two x-intercepts for Δ > 0.
Solve the inequality:
[tex]49-12m>0[/tex] subtract 49 from both sides
[tex]-12m>-49[/tex] change the signs
[tex]12m<49[/tex] divide both sides by 12
[tex]m<\dfrac{49}{12}[/tex]
The values of m that make the graph of y=3x²+7x+m have two x-intercepts are m less than 49/12.
Explanation:To find the values of m that make the graph of the equation y = 3x² + 7x + m have two x-intercepts, we need to determine when the discriminant is greater than zero. The discriminant can be calculated using the formula b² - 4ac, where a is the coefficient of x², b is the coefficient of x, and c is the constant term. In this case, a = 3, b = 7, and c = m. Setting the discriminant greater than zero and solving for m, we get:
7² - 4(3)(m) > 0
Simplifying the equation, we have:
49 - 12m > 0
Now, we can solve for m by isolating it on one side of the inequality:
-12m > -49
m < 49/12
Therefore, for any value of m that is less than 49/12, the graph of y = 3x² + 7x + m will have two x-intercepts.
Learn more about Quadratic Equations here:
https://brainly.com/question/30098550
#SPJ2
The average rate of change from x = -2 to x = 6 for the function shown in the graph is______?
Answer: -1/2
Step-by-step explanation:
Answer:
-1/2 (2nd option)
Step-by-step explanation:
Just did it on Edg 2021
what answer would this be? Question is attached
Answer:
0.65m
Step-by-step explanation:
Given the function as
[tex]P(h)=P_0*e^{-0.00012h}[/tex]
Lets take the air pressure at the surface of the Earth to be x
[tex]P_0=x[/tex]
Then 65% of this will be the air pressure P(h)
[tex]P(h)=\frac{65}{100} *x=0.65x[/tex]
The function will be
[tex]0.65x(h)=x*e^{-0.00012h}[/tex]
Divide both sides by x
[tex]0.65=e^{-0.00012h}\\ \\\\e=2.71828182846\\\\\\0.65=2.7182818284^{-0.00012h} \\\\\\0.65=0.99989h\\\\\\\frac{0.65}{0.99989} =\frac{0.99989h}{0.99989} \\\\\\h=0.65m[/tex]
Option: A is the correct answer.
A. 3589.9 m
Step-by-step explanation:The function which determines the pressure h height above the surface of earth is:
[tex]P(h)=P_0\cdot e^{-0.00012h}[/tex]
where [tex]P_0[/tex] is the pressure at the surface of the earth.
We are asked to find the height when the pressure above the surface of earth is equal to 65% of the pressure at the surface of earth.
i.e.
[tex]P_0\cdot e^{-0.00012h}=0.65\cdot P_0\\\\i.e.\\\\e^{-0.00012h}=0.65\\\\i.e.\\\\e^{0.00012h}=\dfrac{1}{0.65}\\\\i.e.\\\\\ln(e^{0.00012h}}=\ln(\dfrac{1}{0.65})\\\\i.e.\\\\0.00012h=\ln(\dfrac{1}{0.65})\\\\i.e.\\\\h=3589.8576\ m[/tex]
which is approximately equal to:
[tex]h=3589.9\ m[/tex]
PLEASE HELP I DONT UNDERSTAND
Answer:
B.
-4, 1, 5, 8
Step-by-step explanation:
Your domain is your set of x values.
Your points are as follows:
(-4, 8)
(8, 10)
(5, 4)
(1, 6)
(5, -9)
Your x-values here are -4, 8, 5, 1, and 5. Your domain only consists of unique x-values, so your domain consists of -4, 8, 5, and 1.
In circle P, which pair of arcs are adjacent arcs?
Answer: BA and AE are adjacent angles
Answer:
Arc AB and AE are adjacent arc.
Step-by-step explanation:
Given; A circle P with diameter AD and BE.
To find : which pair of arcs are adjacent arcs.
Solution : We have given A circle P with diameter AD and BE.
Arc length is the distance between two points along a section of a curve.
Here curve AB and AE are two arc which are adjacent to each other.
Therefore, Arc AB and AE are adjacent arc.
Solve the equation for x by graphing. -4x-1=5^x+4
Answer:
x=-1.282
Step-by-step explanation:
To solve the equation [tex]-4x-1=5^x+4[/tex] by graphing, you have to plot graphs of two functions:
[tex]y=-4x-1\\ \\y=5^x+4[/tex]
The x-coordinate of the point of intersection is the solution of the equation.
The graph of the function [tex]y=-4x-1[/tex] is shown in attached diagram with red line and the graph of the function [tex]y=5^x+4[/tex] is shown with blue curve.
The point of intersection has approximate coordinates (-1.282, 4.127), so the solution (correct to three decimal places) of the equation is x=-1.282
As the loan amortizes and nears the end, the majority of the payment is used to pay the ___
Answer: principle APEX
Step-by-step explanation:
As the loan amortizes and nears the end, the majority of the payment is used to pay the principal is the correct answer.
What is a loan?A loan is a commitment that you (the borrower) will receive money from a lender, and you will pay back the total borrowed, with added interest, over a defined time period. A loan may be secured by collateral such as a mortgage or it may be unsecured such as a credit card.
For the given situation,
At the beginning of the loan's term, the majority of the payments are given to interest and just a small part to the loan's principal.
Near the end of the loan's term, the majority of each payment given to principal, and only a small portion is allocated to interest.
Hence we can conclude that as the loan amortizes and nears the end, the majority of the payment is used to pay the principal is the correct answer.
Learn more about loan here
https://brainly.com/question/15259527
#SPJ2
Write the standard form of the equation of a line if the point on the line nearest to the origin is at (6, 8).
Answer:
[tex]\large\boxed{y=\dfrac{4}{3}x}[/tex]
Step-by-step explanation:
The line passes through the origin has an equation y = mx
m - slope
The formula of a slope of a line passes through the origin
and a point (x, y):
[tex]m=\dfrac{y}{x}[/tex]
We have the point (6, 8). Substitute:
[tex]m=\dfrac{8}{6}=\dfrac{8:2}{6:2}=\dfrac{4}{3}[/tex]
Finally:
[tex]y=\dfrac{4}{3}x[/tex]
27x = 9x − 4
x = 8
x = 4
x = −4
x = −8
The solution to the equation 27x = 9x - 4 is x = -2/9, which is not listed in the provided options. None of the options (8, 4, -4, -8) are correct, and the correct solution can be verified by substituting back into the original equation.
The correct option is (d).
When solving the equation 27x = 9x − 4, we aim to find the value of x that satisfies the equation. To do this, we can follow a step-by-step approach:
First, we subtract 9x from both sides of the equation to get 18x = -4.Next, we divide both sides of the equation by 18 to isolate x, which results in x = -4/18.Simplifying the fraction gives us the solution x = -2/9.We must then verify if any of the provided options (8, 4, -4, -8) match our solution. As none of these values is equal to -2/9, none of the options provided is correct.
To check our solution, we can substitute x back into the original equation and verify that it leads to an identity, confirming that we have found the correct solution. Here, our verification step would show that 27(-2/9) is indeed equal to 9(-2/9) - 4, verifying the solution is correct.
complete question given below:
27x = 9x − 4
a.x = 1/8
b.x = 4
c.x = −4/3
d.x = −2/9
Solve xto the 2nd power= 121.
A. 60.5
B.-11
C.11
D.+11
-
Answer:
x = -11 and x = 11Step-by-step explanation:
[tex]x^2=121\to x=\pm\sqrt{121}\\\\x=\pm11\qquad\text{because}\ 11^2=(-11)^2=121\\\\==================\\\\\sqrt{a}=b\iff b^2=a[/tex]
Answer:
the answer is D
Step-by-step explanation:
i hope this helps
The sum of a number and 20 is no more than the sum of the square of the number and 9.
Which of the following inequalities can be used to determine this unknown number?
A. x + 20 < (X + 9)2
B.
X+ 20 x2 + 9
C.
X+ 20 = (x + 9)2
D.
X + 20 < x2 +94
A is the correct answer.
break down the word problem.
You also have to recognize key words which figure into mathematical symbols.
ex. sum of a number and 20 is x+20
square of the number and 9 is (x+9)^2
please vote my answer brainliest! thanks.
Joe has one book each for algebra, geometry, history, psychology, Spanish, English and Physics in his locker. How many different sets of three books could he choose?
Answer:
There are 35 different sets of 3 books Joe could choose
Step-by-step explanation:
* Lets explain how to solve the problem
- Combination is a collection of the objects where the order doesn't
matter
- The formula for the number of possible combinations of r objects from
a set of n objects is nCr = n!/r!(n-r)!
- n! = n(n - 1)(n - 2)................. × 1
Lets solve the problem
- Joe has one book each for algebra, geometry, history, psychology,
Spanish, English and Physics in his locker
∴ He has seven books in the locker
- He wants to chose three of them
∵ The order is not important when he chose the books
∴ We will use the combination nCr to find how many different sets
of three books he can choose
- The total number of books is 7
∴ n = 7
∵ He chooses 3 of them
∴ r = 3
∵ 7C3 = 7!/3!(7 - 3)! = 7!/3!(4!)
∴ [tex]7C3=\frac{(7)(6)(5)(4)(3)(2)(1)}{[(3)(2)(1)][(4)(3)(2)(1)]}=35[/tex]
∴ 7C3 = 35
* There are 35 different sets of 3 books Joe could choose
What is the following quotient? sqrt 6 + sqrt 11 / sqrt 5 +sqrt 3
The answer is B) Link below
Answer:
B
Step-by-step explanation:
I just did it
What is the value of 2 over 3 to the power of 0 to the power of -3
Answer:
[tex]((\frac{2}{3})^0)^{-3}=1[/tex]
Step-by-step explanation:
We need to find the value of [tex]((\frac{2}{3})^0)^{-3}[/tex]
Solving:
We know, [tex](a^b)^n = a^{b*n}[/tex]
[tex]((\frac{2}{3})^{0*-3})[/tex]
[tex](\frac{2}{3})^0[/tex]
a^0 = 1
so,
[tex](\frac{2}{3})^0=1[/tex]
So, the value of [tex]((\frac{2}{3})^0)^{-3}=1[/tex]
What is the sum of the geometric sequence 1,-6,36 if there are 6 terms
Answer:
The sum of the six terms is 9331
Step-by-step explanation:
* Lets explain what is the geometric sequence
- There is a constant ratio between each two consecutive numbers
- Ex:
# 5 , 10 , 20 , 40 , 80 , ………………………. (×2)
# 5000 , 1000 , 200 , 40 , …………………………(÷5)
* General term (nth term) of a Geometric sequence:
# U1 = a , U2 = ar , U3 = ar² , U4 = ar³ , U5 = ar^4
# [tex]U_{n}=ar^{n-1}[/tex], where a is the first term , r is the constant
ratio between each two consecutive terms, n is the position
of the term
- The sum of n terms of the geometric sequence is:
[tex]S_{n}=\frac{a(1-r^{n})}{1-r}[/tex] , where n is the number of the terms
a is the first term and r is the common ratio
* Lets solve the problem
∵ The geometric sequence is 1 , -6 , 36 , .........
∵ The common ratio r = U2/U1
∵ U1 = 1 and U2 = -6
∴ r = -6/1 = -6
∵ The first term is 1
∴ a = 1
∵ There are 6 terms in the sequence
∴ n = 6
∴ The sum = [tex]\frac{1[1 - (-6)^{6}]}{1-6}=\frac{1[1-46656]}{-5}=\frac{-46655}{-5}=9331[/tex]
* The sum of the six terms is 9331
Question 2 of 10
2 Points
If you vertically stretch the quadratic parent function, Fx) = x2, by multiplying
by 7, what is the equation of the new function?
O A. G(x) = x2 - 7"
O B. G(x) = (x + 7)2
O C. G(x) = (7x)2
O D. G(x) = 7x2
SUBMIT
Answer:
D. G(x) = 7x2
Step-by-step explanation:
Given a function f(x), the function kf(x) is stretched by a factor of k. In this case, if we stretch the function f(x) = x^2 by a factor of 7, the new function is going to be:
g(x) = 7x^2. Therefore, the correct option is option D.
(9y+7)
Find the value of y and
the measures of all
angles.
(2y+98)°
Answer:
Both obtuse angles - 124°
Both acute angles - 56°
Step-by-step explanation:
The two given obtuse angles are equal. Therefore you get an equation
[tex]9y+7 = 2y+98\\7y=91\\y=13[/tex]
So the obtuse sizes of the two given angles are [tex]13*9+7=2*13+98=124[/tex]°
And the sizes of the acute angles are [tex]180-124=56[/tex]°
Without a clear relationship between the expression (9y+7) and the angle measurement (2y+98)°, we cannot find a unique value for y. However, the measure of the angle would vary with y according to the formula (2y+98)°.
Explanation:The given expression is (9y+7) and the measure of the angle is (2y+98)°. We aren't given a specific equation that links the expression to the measure of the angle, so we cannot find a unique value for y. However, if a particular relationship between the expression and the measure of the angle is provided, such as them being equal, we can use algebraic methods to solve for y.
As for measures of angles, in general, if we know the value of y, we can substitute that into the (2y+98)° to find the specific angle. Without knowing the value of y or a particular relationship between (9y+7) and (2y+98)°, we can say that the measure of the angle varies with y according to the formula (2y+98)°.
Learn more about Algebraic Representation here:https://brainly.com/question/21512696
#SPJ11
Mr. Wilson wrote the function fx) = 7x - 15 on the chalkboard. What is the value of this function for f(6)?
A 27
B 37
C 42
D 57
Answer: 27
Step-by-step explanation:
F(6)=42-15=27
Answer:
A 27
Step-by-step explanation:
f(x) = 7x - 15
Let x=6
f(6) = 7*6 -15
= 42 -15
= 27
Graph the numbers 3, -5/2, 0, 3/4 on a number line
Answer:
Step-by-step explanation:
If it's any help, these numbers, rearranged in ascending order, are
-5/2, 0, 3/4, 3.
Place a bold dot at -5/2 on your number line. This is halfway between -2 and -3. Next, place such a dot at 0. Next, place a dot at 3/4, which is between 0 and 1 but closer to 1. Last, place a dot at 3.